Zákon č. 595/2003 Z.z. o dani z príjmov s komentárom - Brnová, Miroslava
Zákon č. 595/2003 Z.z. o dani z príjmov v znení ďalších zákonov ... a zákonov č.406/2011 Z.z., č. 547/2011 Z.z a č. 548/2011 Z.z.